The Waves of Words: Literature of 3/11 in and around Ruth Ozeki's A Tale of the Time Being. (20th November 2015) - Usui, Masami
Abstract: Literature has often been turned to during global chaos of world wars, terrorism, and unprecedented natural disasters due to rapidly advancing technology. As Atomic Bombs in Hiroshima and Nagasaki in 1945 created Atomic Bomb literature, 9/11 in New York created 9/11 literature. Named 3/11 after 9/11, the giant earthquake and tsunami that hit North-East Japan on 11 March 2011 founded the 3/11 literature. This group of Japanese writers could not help writing, directly or indirectly, on 3/11, initiating the foundation of a 3/11 literature3/11. It was Ruth Ozeki on the other side of the ocean gave the voice to 3/11, bycompleting her novel. In and around Ozeki's The Tale for the Time Being (2013), therefore, there is a shared consciousness of making waves in the form of literature. 3/11 literature is more complicated than Atomic Bomb literature or 9/11 literature. Atomic Bombs and 9/11 are also interrelated as far as both of them represent monstrous wars which left even the unwounded with scars in this modernized and globalized world. Atomic Bombs and 3/11 are furthermore connected because 3/11 resulted in the crisis of the Fukushima Nuclear Power Plant. 3/11 brings to us not only the reality of the visible physical destruction and disaster, but also the invisible nuclear pollution and influence on our lives, intensifyings the inquiry into the reason for and the meaning of existence and life. Ultimately, contemporary writers are making waves of words, and those words are echoing in and around Ozeki's A Tale of the Time Being, which examines the interwoven psychological conflicts issued by 3/11 spreading across the ocean and over the generations.